2018
DOI: 10.14202/vetworld.2018.355-362
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of bacteria causing mastitis in small ruminants and their susceptibility to antibiotics, honey, essential oils, and plant extracts

Abstract: Aim:The present work aims to isolate and identify bacteria that cause mastitis in small ruminants and evaluates the antibacterial activity of some antibiotics, honey, essential oils, and plant extracts.Materials and Methods:A total of 289 milk samples were collected from udder secretions of sheep (n=189) and goat (n=100) from El-Fayoum, Beni-Suef, and Giza governorates. Screening subclinical mastitis (SCM) was done using California Mastitis Test (CMT); identification of the isolates was achieved using Gram’s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 36 publications
4
27
1
Order By: Relevance
“…In the present study, the prevalence of clinical and subclinical mastitis was 23% and 40% respectively. This result is in contrast with that of Abdalhamed et al (2018) who recorded 7% and 11% prevalence rates of clinical and subclinical mastitis in goats based on the results of CMT. Previous study by Ebrahimi et al (2007) reported mastitis was found in goats only with low prevalence (5.25%).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the prevalence of clinical and subclinical mastitis was 23% and 40% respectively. This result is in contrast with that of Abdalhamed et al (2018) who recorded 7% and 11% prevalence rates of clinical and subclinical mastitis in goats based on the results of CMT. Previous study by Ebrahimi et al (2007) reported mastitis was found in goats only with low prevalence (5.25%).…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have been published on antibiotic resistant bacteria in sheep milk, both in milk from individual sheep, and in bulk milk, and also in raw sheep milk cheese. Studies were focused on resistant zoonotic bacteria, commensal bacteria, mastitis-causing bacteria, and specific resistances, including methicillin-resistant S. aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Gram-negative bacteria, and vancomycin-resistant enterococci (VRE) (Abdalhamed et al, 2018;Abo-Shama, 2014;Alian et al, 2012;Ariza-Miguel et al, 2014;Azara et al, 2017;Burriel, 1997;Carfora et al, 2016;Ceniti et al, 2017;Corrente et al, 2003;Giacinti et al, 2017;Jiménez et al, 2013;Lollai et al, 2016;Macori et al, 2017;Mousavi et al, 2014;Obaidat et al, 2018;Onni et al, 2011;Ortigosa et al, 2008;Sanciu et al, 2012;Solomakos et al, 2009;Spanu et al, 2012Spanu et al, , 2014. Comparing literature data on antibiotic resistant bacteria in raw sheep milk is complicated because of several differences, e.q.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The study conducted on clinical examination, the incidence of pseudomonas spp. was found to be 5.88% sheep and 7% human respectively (21).…”
Section: Prevalence Of Bacteria Crossed From Sheep To Humanmentioning
confidence: 97%